Moderate‐to‐Vigorous Physical Activity Is Associated With Higher Muscle Oxidative Capacity in Older Adults. Issue 8 (22nd May 2019) - Adelnia, Fatemeh; Urbanek, Jacek; Osawa, Yusuke; Shardell, Michelle; Brennan, Nicholas A.; Fishbein, Kenneth W.; Spencer, Richard G.; Simonsick, Eleanor M.; Schrack, Jennifer A.; Ferrucci, Luigi
Abstract : BACKGROUND: Age‐related decline in muscle oxidative capacity reduces muscle function and physical performance, leading to disability and frailty. Whether age‐related decline in oxidative capacity is modified by exercise and other lifestyle practices is unclear. Therefore, we tested the hypothesis that physical activity is associated with better oxidative capacity, independent of age. DESIGN: Cross‐sectional study performed in the Baltimore Longitudinal Study of Aging, conducted by the Intramural Research Program (IRP) of the National Institute on Aging (NIA). SETTING: NIA IRP Clinical Research Unit, Baltimore, MD. PARTICIPANTS: Participants included 384 adults (54.7% women), aged 22 to 92 years, seen between 2013 and 2017. MEASUREMENTS: Muscle oxidative capacity was measured in vivo using phosphorous magnetic resonance spectroscopy. We determined the postexercise time constant (τPCr ; in seconds) for phosphocreatine (PCr) recovery, with lower values of τPCr, (ie, more rapid recovery of PCr levels after exercise) reflecting greater oxidative capacity. Time spent in moderate‐to‐vigorous physical activity (MVPA) was assessed using wearable accelerometers that participants wore 5.9 ± 0.9 consecutive days in the free‐living environment. RESULTS: In linear regression models, higher τPCr was associated with older age (standardized β = .39; P < .001) after adjusting for sex, race, height, and weight. After including MVPA as an independent variable, the standardized regression coefficient of age decreased by 40%, but remained associated with τPCr (βage = .22; P < .001) and had a smaller standardized regression coefficient than MVPA (βMVPA = −.33; P < .001). After adjusting for health status, education, and smoking history, the standardized regression coefficient for age decreased 12% (βage = .20; P = .003), while the standardized coefficient for MVPA decreased only 3% (βMVPA = −.32; P < .001). CONCLUSION: Study findings suggest that MVPA is strongly associated with muscle oxidative capacity, independent of age, providing mechanistic insights into the health benefits of exercise in older age. J Am Geriatr Soc 67:1695–1699, 2019